PENGARUH INTESITAS CAHAYA TERHADAP TANAMAN KELAPA SAWIT DI FASE PEMBIBITAN (Elaeis guineensis jacq) - Kani, Almunazza; Rama Adrian; Celine Louise Adelia Purba; Hari Gunawan; Givin Glenasfi Sinulingga; Julfan Efendi (Fakultas Pertanian Universitas Janabadra, 2026)
This study aims to evaluate the effect of light intensity and fertilization on the height and stem diameter growth of oil palm seedlings (Elaeis guineensis Jacq) at 16 weeks of age. The study was conducted under controlled conditions with varying light intensities and types of fertilizer applied to the seedlings. The results showed that an increase in light intensity significantly increased seedling height, with optimal growth recorded at an intensity of 2000 lux, reaching 19.15 cm. In addition, fertilization also had a positive effect on stem diameter, where 15 g of fertilizer produced a maximum diameter of 0.50 cm. Statistical analysis using the BNT test showed significant differences between treatments at a 5% rate. These findings indicate that a combination of good lighting and proper fertilization is very important to support oil palm seedling growth, providing guidance for better cultivation practices in the field.